2023
DOI: 10.3389/fendo.2023.1086731
|View full text |Cite
|
Sign up to set email alerts
|

Sheehan syndrome: Cardiovascular and metabolic comorbidities

Abstract: Sheehan syndrome (SS) caused by postpartum hemorrhage leads to partial or complete pituitary hormone deficiency. In addition to lipid and glucose abnormalities, patients with SS have increased body fat, insulin resistance (IR), coagulation abnormalities, increased leptin concentration, low-grade inflammation, and endothelial dysfunction that predispose them to cardiovascular diseases. Untreated growth hormone (GH) deficiency, hypogonadism, and excess glucocorticoid use are considered risk factors for these abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Moreover, hypopituitarism can be fatal owing to a decrease in the hor-mone levels if the disease is not properly diagnosed or treated. In particular, a previous study revealed that hypopituitarism may also deteriorate the condition of concomitant disorders (5). Therefore, an appropriate diagnosis and management of hypopituitarism are important.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypopituitarism can be fatal owing to a decrease in the hor-mone levels if the disease is not properly diagnosed or treated. In particular, a previous study revealed that hypopituitarism may also deteriorate the condition of concomitant disorders (5). Therefore, an appropriate diagnosis and management of hypopituitarism are important.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive growth hormone replacement negatively affects glucose tolerance, suggesting a potential risk for metabolic syndrome and diabetes. 5 Patients with pituitary insufficiency have a high incidence of cardiovascular events. 21 A report on the assessment of the risk of cardiovascular events in Sheehan syndrome using coronary artery calcification revealed that the Sheehan syndrome group had significantly more coronary artery calcification than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormones also have insulin‐antagonistic effects. Excessive growth hormone replacement negatively affects glucose tolerance, suggesting a potential risk for metabolic syndrome and diabetes 5 . Patients with pituitary insufficiency have a high incidence of cardiovascular events 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations